Analisis Kurikulum Berbasis Kompetensi (KBK)/Kurikulum 2004 - Namiyah Fitriani; Dian Afrilianti (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2025)
Education is a fundamental element in human life and plays an important role in building a better country. This article discusses the importance of curriculum in education, particularly the Competency-Based Curriculum (KBK) implemented in Indonesia. By integrating learning that supports holistic character development, the government seeks to create a young generation that is not only academically intelligent, but has good skills and character. This research uses a qualitative method with a literature study approach to analyze the 2004 curriculum, which is a transition from the previous curriculum. Through data collection and analysis from various sources, this article explores the definition, characteristics and implementation of the KBK, as well as the advantages and obstacles faced in its implementation. The results show that while the KBK has many advantages, such as the development of student abilities and student-centered learning, there are challenges in terms of teacher professionalism and consistency in the application of competency standards. This research is expected to provide new insights into curriculum development in Indonesia and its contribution to improving the quality of national education.